Modelling the Role of Active Biomass on the Fate and Transport of a Heavy Metal in the Presence of Root Exudates - K. V. Nedunuri; L. E. Erickson; R. S. Govindaraju (Journal of Hazardous Substance Research, 1998)
The influence of active biomass in immobilizing heavy metals in the soil rhizosphere is investigated through mechanistic models. The movement of water in the soil is modeled using Richards equation. An advection-dispersion equation, with a sink term for metal uptake by biomass, is used for modeling the fate and transport of lead. This sink term represents the nonlinear kinetics of metal adsorption to the biomass that is partitioned into mobile and stationary fractions within the soil. Transport of the mobile biomass fraction is modeled by an advection-dispersion equation, with a source term that is based on Monod growth kinetics, and a linear sink term for endogenous decay. The movement of metal in association with mobile biomass is also included as a transport mechanism for lead. Root exudates serve as carbon substrate for the biomass growth, and their transport is modeled in a similar way as that of the biomass. A hypothetical one-dimensional vertical soil column containing metal, biomass and a carbon substrate is used for analyzing lead movement. Model simulations demonstrate the influence of water content, growth rate of biomass, partitioning coefficient of biomass between soil and aqueous phase, and partitioning coefficient of metal between biomass and aqueous phase of the soil on fate and transport of lead. The extent of immobilization of lead in soil is found to be dependent on the growth of biomass, which in turn depends on the availability of root exudates in the rhizosphere. Apart from analyzing different scenarios, such a model can be used for designing future experiments.
Keywords: heavy metals; rhizosphere; mathematical modeling; kinetics; biomass